Ligand-induced Trafficking of the Sphingosine-1-phosphate Receptor EDG-1 - Liu, Catherine H. (The American Society for Cell Biology, 1999)
The endothelial-derived G-protein–coupled receptor EDG-1 is a high-affinity receptor for the bioactive lipid mediator sphingosine-1-phosphate (SPP). In the present study, we constructed the EDG-1–green fluorescent protein (GFP) chimera to examine the dynamics and subcellular localization of SPP–EDG-1 interaction. SPP binds to EDG-1–GFP and transduces intracellular signals in a manner indistinguishable from that seen with the wild-type receptor. Human embryonic kidney 293 cells stably transfected with the EDG-1–GFP cDNA expressed the receptor primarily on the plasma membrane. Exogenous SPP treatment, in a dose-dependent manner, induced receptor translocation to perinuclear vesicles with a τ(1/2) of ∼15 min. The EDG-1–GFP–containing vesicles are distinct from mitochondria but colocalize in part with endocytic vesicles and lysosomes. Neither the low-affinity agonist lysophosphatidic acid nor other sphingolipids, ceramide, ceramide-1-phosphate, or sphingosylphosphorylcholine, influenced receptor trafficking. Receptor internalization was completely inhibited by truncation of the C terminus. After SPP washout, EDG-1–GFP recycles back to the plasma membrane with a τ(1/2) of ∼30 min. We conclude that the high-affinity ligand SPP specifically induces the reversible trafficking of EDG-1 via the endosomal pathway and that the C-terminal intracellular domain of the receptor is critical for this process.